Defining Stress Thresholds of Granite Failure Process Based on Acoustic Emission Activity Parameters - Xingdong Zhao; Lei Deng; Jitao Xu (Shock and Vibration)
In order to study the crack closure stress threshold σcc of hard rock, crack initiation stress threshold σci, stress threshold σcs of crack interaction, and damage stress threshold σc d, uniaxial compression test was carried out on granite samples. Stress sensor and dynamic strain gauge are used to measure the load, longitudinal, and lateral deformation of rock in real time. The acoustic emission characteristic parameters of rock fracture process are obtained by using the acoustic emission system. According to the change rule of the AE event rate, cumulative energy, energy rate, duration, and amplitude in the whole process of granite sample fracture, the stress threshold (σcc, σci, σcs, and σc d) of each loading stage in the process of rock sample fracture is obtained. The relationship between the stress threshold (σcc, σci, σcs, and σc d) of each stage and the uniaxial compressive strength σUCS of rock samples in the whole process of fracture is analyzed, which shows that the deformation characteristics and crack evolution law of the rock are unified. The research results can provide some reference for further understanding of rock damage evolution mechanism in engineering field.